2020
DOI: 10.1111/hepr.13553
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes of liver function and hepatitis B reactivation in COVID‐19 patients with pre‐existing chronic hepatitis B virus infection

Abstract: Aim: With the current coronavirus disease (COVID-19) pandemic and high endemic levels of chronic hepatitis B virus (HBV) infection worldwide, it is urgent to investigate liver function changes of COVID-19 patients with chronic HBV infection, and how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in turn affects the course of chronic HBV infection. Method: We undertook a retrospective study based on 347 COVID-19 patients (21 vs. 326 with vs. without chronic HBV infection). With the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 21 publications
0
74
0
2
Order By: Relevance
“…HBV coinfection did not affect the course and prognosis of COVID-19. In another study by Liu et al [ 23 ], 21 (6.4%) patients with COVID-19 and HBV coinfection were included, and 51 matched COVID-19 patients without HBV were used for comparison. They explored the independent impact of chronic HBV infection on the progression to severe COVID-19 and found that HBV did not delay SARS-CoV-2 shedding and did not increase the risk of progression and poor outcomes related to SARS-CoV-2.…”
Section: Impact Of Hbv On Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…HBV coinfection did not affect the course and prognosis of COVID-19. In another study by Liu et al [ 23 ], 21 (6.4%) patients with COVID-19 and HBV coinfection were included, and 51 matched COVID-19 patients without HBV were used for comparison. They explored the independent impact of chronic HBV infection on the progression to severe COVID-19 and found that HBV did not delay SARS-CoV-2 shedding and did not increase the risk of progression and poor outcomes related to SARS-CoV-2.…”
Section: Impact Of Hbv On Covid-19mentioning
confidence: 99%
“…In a retrospective study[ 23 ] of 21 patients with SARS-CoV-2 and HBV coinfection, 19 patients were tested for HBV DNA viral load at least twice during hospitalization. Of the 19 patients, three patients developed HBV reactivation and manifested as a rapid increase in HBV DNA viral load from undetectable to a high level.…”
Section: Impact Of Sars-cov-2 On Hbvmentioning
confidence: 99%
“…In a retrospective study, the authors analyzed liver function parameters including ALT, AST and TBIL in COVID-19 patients with or without HBV infection and found no significant differences between the two groups[ 56 ]. Another study reached a similar conclusion and further proved the longitudinal changes of median values for liver biochemistries were not significantly different between the two groups either[ 57 ]. These findings indicated that SARS-CoV-2 will not exacerbate liver injury in patients with HBV co-infection.…”
Section: Introductionmentioning
confidence: 64%
“…In their cohort, COVID-19 cases with HBV coinfection had higher levels of ALT, AST, TBIL and ALP than the COVID-19 cases without HBV coinfection, showing that inactive HBV carriers with SARS-CoV-2 coinfection are at risk of greater liver injury. Moreover, SARS-CoV-2 was reported to induce HBV reactivation, which may cause severe liver injury in patients with coinfection[ 57 , 59 ]. In addition, a case of COVID-19 with Epstein-Barr virus coinfection was reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we reported the sequential levels of HBV-related markers during the acute infection of SARS-CoV-2. Previous studies on patients coinfected with SARS-CoV-2 and HBV have shown that the existence of coinfection could not aggravate the liver injury or extend the duration of hospitalization compared with HBV infection alone ( Chen et al, 2020 ; Liu et al, 2020 ). However, these studies failed to depict levels of all HBV-related markers during the infection and clearance of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 97%